(untitled) (Ustozlar uchun, 2026)
This text offers a philosophically dense, interdisciplinary examination of the contemporary discourse on technology, framing it as an unresolved tension between human augmentation and existential compression. It traces the externalization of cognition through large-scale AI systems—particularly transformer-based language models—which shift meaning-making from biological to statistical substrates, blurring syntax/semantics and simulation/understanding while mirroring predictive-coding theories in neuroscience. The analysis extends to the geological materiality of digital infrastructure, the convergence of biotech–nanotech–infotech that dissolves organism/artifact boundaries, and the temporal flattening induced by attention economies that privilege hyperstimulation over sustained reflection. It critiques surveillance capitalism’s evolution into preemptive governance of possibility, contrasts it with open-source disruption and quantum threats to cryptography, and underscores biophysical energy ceilings that constrain computational scalability. Ultimately, the discourse emerges as constitutively aporetic: a site where modernity confronts its own reconstituted conditions of agency, freedom, and finitude amid planetary-scale rewiring of cognition, matter, energy, and time—without resolution into utopian or dystopian certainties.